2021
DOI: 10.3389/fnut.2021.748031
|View full text |Cite
|
Sign up to set email alerts
|

Origanum majorana L.: A Nutritional Supplement With Immunomodulatory Effects

Abstract: Origanum majorana L. is an aromatic herb that has been grown in several Mediterranean countries since ancient times, but became popular during the Middle Ages as a medicinal plant and seasoning ingredient. O. majorana has many pharmacological effects, but its immunoreactive components and mechanisms are still unclear. In this study, four compounds were isolated and identified from O. majorana by a spectral analysis, including 1H and 13C-NMR. They were 1H-indole-2-carboxylic acid (1), (+)-laricresol (2), (+)-is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…RAW264.7 cells were cultured by the assay of Senye Wang ( 32 ). At 37°C in a humidified incubator with a 5% CO2 atmosphere, cells were grown in DEME high glucose medium with 10% fetal bovine serum (FBS, Gibco, USA), 100 U/mL penicillin and 100 μg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…RAW264.7 cells were cultured by the assay of Senye Wang ( 32 ). At 37°C in a humidified incubator with a 5% CO2 atmosphere, cells were grown in DEME high glucose medium with 10% fetal bovine serum (FBS, Gibco, USA), 100 U/mL penicillin and 100 μg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from extensively utilizing it as a condiment to flavour meats, salads, and soups, it was also found that this herb has a great potential for industrial applications as an antimicrobial and antioxidant ingredient. In the food industry, the distilled oil is frequently applied to increase storing stability and reduce microbial contamination [ 1 , 2 ]. The essential oil is also used in perfumery, pharmaceuticals and cosmetics.…”
Section: Introductionmentioning
confidence: 99%
“…Tese proinfammatory cytokines are crucial agents as immunomodulators in the infammatory response of tissue cells. ROS acts as an important signaling molecule for immune regulation in macrophages, and its production is closely related to the NF-κB signaling pathway [39]. It is produced by activated macrophages and can trigger the inhibitory IκB kinase, leading to the phosphorylation of IκB and to the formation of heterodimer NF-κB which will cross the nuclear membrane to bind the genomic region and promote the generation of infammatory factors, thus playing an essential role in the regulation of the immune signal transduction network [40].…”
Section: Discussionmentioning
confidence: 99%